The Influence of Gross Enrollment Ratio (GER) on the Literacy and Inclusion Index: A Case Study of Islamic Finance in Indonesia - Zulfikar Hasan; Ahmad Azam Sulaiman; Mutia Rosiana Nita Putri (Unisia, 2021)
The inclusion and literacy of Islamic finance is an index that can use as a guide in assessing whether people living in a country know about Islamic finance. Multiple variables can conclude whether a nation knows Islamic banking. The Financial Services Authority does a review that can use as additional analysis on the knowledge of the Indonesian personalities about Islamic Banking. Overall, the Third National Financial Literacy Survey (SNLIK) accompanied by the Financial Services Authority (OJK) this year revealed that the financial literacy index equaled 38.03%, including the financial inclusion index of 76.19%. Based on geographical levels, during urban financial literacy index equaled 41.41% and economic inclusion of urban ranges amounted to 83.60%. OJK will use the results of the 2019 financial literacy survey to improve the national financial literacy developing policy that is further practical and targeted. In comparison, the literacy index and financial inclusion of rural communities were 34.53% and 68.49%. This pattern developed compared to the results of the 2016 OJK survey, precisely the financial literacy index 29.7% and the financial inclusion index 67.8%. The questionnaire effects further designated that based on gender literacy index and economic inclusion of men were 39.94% and 77.24%, comparatively higher than women at 36.13% and 75.15%.